Mitos Kecantikan sebagai Inspirasi Penciptaan Karya Seni Lukis - Marina Anjani; Insanul Qisti Barriyah; Moh. Rusnoto Susanto; Dwi Susanto (Reslaj : Religion Education Social Laa Roiba Journal, 2022)
The creation of this artwork aims to be able to educate the public about discrimination against women which is often not realized, invite the wider community to stop attitudes and behaviors that discriminate against women, and be able to implement it into the form of painting so that it can be enjoyed by the wider community directly. as well as through print and electronic media. The creation of this painting is carried out using the exploration method, namely in the form of exploration of ideas and concepts, exploration of forms, exploration of media and techniques, aesthetic exploration, and data obtained from research conducted previously so as to produce primary and secondary data. In the creation of a painting with the title “Beauty Myths as Inspiration for the Creation of Paintings”, an embodiment of painting is produced with canvas as the main media with sizes ranging from 80x100 Cm, 130x100 Cm, to 120x100 Cm. With the creation of works of art regarding forms of discrimination against women, knowledge and lessons can be learned from these paintings. Keywords: Myth, Beauty, Inspiration, Creation, Art Painting